2015
DOI: 10.17223/20710410/29/4
|View full text |Cite
|
Sign up to set email alerts
|

Problems, Solutions and Experience of the First International Student’s Olympiad in Cryptography

Abstract: A detailed overview of the problems, solutions and experience of the first international student's Olympiad in cryptography, NSUCRYPTO'2014, is given. We start with the rules of participation and the description of rounds. All 15 mathematical problems of the Olympiad and their solutions are considered in detail. The problems are about differential characteristics of S-boxes, S-box masking, relations between cyclic rotation and additions modulo 2 and 2 n , special linear subspaces in F n 2 , the number of solut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…A special parameter Q considered in the problem is called the linear branch number of a transformation [11]. This problem is a linear cryptanalysis equivalent of the problem "A special parameter" of NSUCRYPTO'2014 [2], where the differential branch number was discussed.…”
Section: Solutionmentioning
confidence: 99%
“…A special parameter Q considered in the problem is called the linear branch number of a transformation [11]. This problem is a linear cryptanalysis equivalent of the problem "A special parameter" of NSUCRYPTO'2014 [2], where the differential branch number was discussed.…”
Section: Solutionmentioning
confidence: 99%
“…where a is a nonzero vector in F n 2 . A vector of values for a given vectorial function F is the vector F (x (1) ), . .…”
Section: Definitionsmentioning
confidence: 99%
“…is a permutation was investigated. It was shown that certain choices of d implies that F is not an APN permutation for even n. It is worth noting that this problem was offered as an unsolved task on NSUCRYPTO competition (see [1] of S. Agievich et. al) and that there were some interesting ideas from participants.…”
Section: Apn Functions and Open Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the algebraic degree of F is equal to 3. The lookup table of F is as follows: F = (0, 12, 6,11,3,25,21,4,17,7,28,9,26,10,2,27,24,22,19,8,14,18,20,23,13,16,5,15,1,30,29,31).…”
Section: Problem "Algebraic Immunity" (Unsolved Special Prize)mentioning
confidence: 99%